Preparation method and application of electrolyte capable of cooperatively adjusting cathode and anode interfaces of aqueous zinc-vanadium battery
By introducing alum additives into the zinc sulfate electrolyte of aqueous zinc vanadium batteries, the interface between zinc-aluminum alloy layer and aluminum-containing electrolyte is formed, the corrosion and dissolution of zinc-aluminum batteries is solved, and the electrochemical performance and cycling stability are significantly improved.
Patent Information
- Application Number
- CN202411329049.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
AI Technical Summary
Due to the spontaneous chemical corrosion and dendrite generation of zinc metal anode, the electrochemical performance decays caused by the spontaneous chemical corrosion of zinc metal anode, and the existing improved methods mainly focus on the compatibility of expensive zinc trifluoromethylsulfonate electrolytes and low-cost zinc sulfate electrolytes. Sex and stability have received less attention.
Alum additive is introduced into low-cost zinc sulfate electrolyte, and the dissolved water is competed with zinc ions for high-priced aluminum ions to form a zinc-aluminum alloy layer, inhibit the growth of zinc dendrites, and form an aluminum-containing electrolyte interface on the surface of the vanadium-based cathode , prevent dissolution.
It significantly improves the electrochemical performance of zinc-vana battery, extends the cycle life and reversibility, enhances the stability of zinc anode and vanadium-based cathode, reduces side reactions, and improves capacity retention.
Smart Images

Figure CN119170895A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous zinc ion secondary batteries, and in particular to a method for preparing an electrolyte capable of synergistically regulating the anode and cathode interfaces of aqueous zinc-vanadium batteries and its application. Background Art
[0002] Aqueous zinc-ion batteries have a high theoretical capacity (820 mAh g -1 and 5855mAh cm -3 ), low redox potential (-0.76V, compared with the standard hydrogen electrode), abundant resources and good environmental benefits, making it a potential alternative to lithium-ion batteries. Aqueous zinc-vanadium batteries have relatively high specific capacity and energy density, and have been recognized as aqueous zinc-ion battery systems with commercial prospects. However, due to the instability of the cathode and anode, aqueous zinc-vanadium batteries face multiple challenges. On the anode side, active zinc metal is plagued by spontaneous chemical corrosion and hydrogen evolution translation in weakly acidic electrolytes. In addition, the uneven surface of bare zinc can lead to uneven zinc nucleation and deposition, resulting in coarse zinc dendrites that can easily pierce the diaphragm and cause short circuits. These problems have seriously hindered the practical application of aqueous zinc-vanadium batteries.
[0003] In response to the problems of zinc metal anode, various effective modification methods have been developed in recent years, such as diaphragm engineering, zinc alloy construction, and electrolyte optimization. In contrast, the introduction of electrolyte additives is a commercial strategy to optimize the zinc anode-electrolyte interface. Functional additives can construct a protective solid electrolyte interphase layer (SEI) or alloy layer in situ. However, many studies have focused on improving the anode without considering the relationship between additives and VO x cathode compatibility, thus limiting the Zn||VO x Improvement of the overall performance of the battery. Recently, it has been found that Zn||VO x The rapid attenuation of battery capacity is mainly due to VO x Irreversible dissolution of cathode in weakly acidic electrolyte (VO x +2yH + →VO x-1 2y+ +yH2O). Another neglected issue is that the current x Battery improvements have mainly focused on the more expensive zinc triflate as the basic electrolyte, while the low-cost and environmentally friendly zinc sulfate electrolyte has received little attention. Therefore, it is of great significance to develop feasible and cost-effective methods to simultaneously enhance the zinc anode and VO in zinc sulfate electrolyte. x The electrochemical stability of the cathode remains challenging. Summary of the invention
[0004] The purpose of the present invention is to provide an electrolyte additive and its application that can synergistically regulate the cathode and anode interfaces of aqueous zinc-vanadium batteries. By adding an alum additive, a protective layer is formed in situ on the cathode and anode surfaces at the same time, thereby improving the electrochemical performance of the entire reversible zinc-vanadium ion battery.
[0005] The present invention obtains an electrolyte by introducing an alum additive into a low-cost zinc sulfate electrolyte, and solves the corrosion and dendrite generation problems of the anode and the dissolution problem of the vanadium-based cathode in the zinc sulfate electrolyte. On the one hand, the high-valent aluminum ions with stronger coordination in the alum compete with the zinc ions for dissolved water, promote the rapid dissolution of the zinc ions, and reduce side reactions. In addition, the zinc-aluminum alloy layer formed in situ during the electrochemical reaction provides a barrier for solvent molecules and anions, inhibiting the growth of zinc dendrites. On the other hand, a cathode electrolyte interface containing aluminum is generated on the cathode surface, which avoids the dissolution of the vanadium-based cathode by polar water molecules and reduces the electrochemical performance attenuation of the zinc-vanadium battery in the zinc sulfate electrolyte.
[0006] To achieve the above object, the present invention provides a method for preparing an electrolyte capable of synergistically regulating the anode and cathode interfaces of an aqueous zinc-vanadium battery, which adopts the following technical scheme:
[0007] (1) Under the assistance of ultrasound, the water-soluble zinc salt solid is completely dissolved in deionized water and cooled to room temperature to obtain a zinc salt solution with a concentration of 0.3-3.0 mol L -1 ; The preferred concentration is 1.5-2.5 mol L -1 ;
[0008] (2) adding an appropriate amount of alum potassium aluminum sulfate additive to the zinc salt solution of step (1), stirring until clear and transparent, to prepare an aqueous electrolyte;
[0009] (3) Preparation of aqueous reversible zinc-vanadium full battery: zinc foil is used as anode, vanadium-based compound is used as cathode material, glass fiber is used as separator, and the aqueous electrolyte prepared in step (2) is introduced to assemble into button batteries (CR2032 type) and soft-pack batteries.
[0010] The zinc salt described in the above step (1) includes zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride and zinc perchlorate.
[0011] The optimal concentration of the alum additive in step (2) is 5-100 mmol L -1As a multifunctional additive, it can protect the cathode and anode at the same time. Aluminum ions are deposited on the zinc anode during charging to form zinc-aluminum alloy, slowing down the growth of zinc dendrites. Aluminum ions have strong coordination ability and form a competitive solvation structure with the solvation structure of hydrated zinc ions, inhibiting the activity of solvated water molecules of zinc ions. A cathode electrolyte interface protective layer containing aluminum is formed on the surface of the vanadium-based cathode, effectively inhibiting the dissolution of the vanadium-based cathode.
[0012] In the aqueous reversible zinc-vanadium full battery described in the above step (3), the zinc metal includes zinc foil, zinc sheet or zinc powder; the vanadium-based compound cathode includes vanadium dioxide, ammonium vanadate or vanadium pentoxide; wherein the vanadium dioxide cathode material is prepared by the following method: 0.1-30g of acetylacetonato vanadium is dispersed in a certain amount of deionized water, and 0.01-10g of sodium dodecyl sulfate is added after stirring. Then, a certain amount of graphene oxide solution is dropped into the above solution, and the mass of graphene oxide is 0.005-3g. After stirring for 0.5h, the solution is transferred to a 0.1-5L polytetrafluoroethylene liner, and a high-temperature reactor is assembled and kept at a constant temperature of 160-210°C for 6-48 hours. Subsequently, the precipitate is centrifuged, washed, and dried to obtain the vanadium dioxide cathode material. The ammonium vanadate cathode material is prepared by the following method: 0.2-10 mol of ammonium metavanadate is dispersed in a certain amount of deionized water, 0.3-10 mol of oxalic acid dihydrate is added after stirring, the solution is transferred to a 0.1-1 L polytetrafluoroethylene liner after stirring for 0.5 h, and a high-temperature reactor is assembled and kept at a constant temperature of 160-210° C. for 1-24 hours. Subsequently, the precipitate is centrifuged, washed, and dried to obtain the ammonium vanadate cathode material; vanadium pentoxide is purchased from Aladdin Company with a purity of 99%.
[0013] The vanadium-based compound cathode electrode sheet in the above step (3) is prepared by the following method: 70wt% of the vanadium-based compound, 20wt% of acetylene black and 10wt% of polyvinylidene fluoride are mixed in N-methylpyrrolidone solvent, and a cathode slurry is obtained after ball milling for 1 hour. The cathode slurry is coated on a titanium foil current collector and vacuum dried at 80°C for 10 hours to prepare a cathode electrode sheet, wherein the mass loading of the active material vanadium oxide is 1 to 30.0 mg cm -2 .
[0014] Furthermore, the present invention provides an application of an electrolyte obtained by the above-mentioned preparation method that can synergistically regulate the anode and cathode interfaces of an aqueous zinc-vanadium battery, which is used to assemble a button battery (CR2032 type) of an aqueous zinc-vanadium battery or a soft-pack battery of an aqueous zinc-vanadium battery.
[0015] In the above application, the assembly method of the button cell (CR2032 type) of the aqueous zinc-vanadium battery is as follows: zinc metal is used as the anode, the vanadium-based compound electrode sheet prepared by the preparation method of the present invention is used as the cathode, glass fiber is used as the diaphragm, and the aqueous electrolyte prepared by the preparation method of the present invention is introduced to assemble into a CR2032 type button cell (CR2032 type).
[0016] In the above application, the soft-pack battery assembly method of the aqueous zinc-vanadium battery is as follows: the battery outer packaging body is made of aluminum-plastic film, the single-piece area of the zinc metal anode is 6cm×6cm, and a total of 6 pieces are made, the single-piece area of the vanadium-based compound cathode sheet is 5cm×5cm, and a total of 5 pieces are made, and the single-piece area of the glass fiber diaphragm is 7cm×7cm, and a total of 10 pieces are made. The cathode, diaphragm, and anode are stacked in sequence, and the aqueous electrolyte prepared by the preparation method described in any one of claims 1-3 is introduced to assemble to obtain an aqueous zinc-vanadium soft-pack battery with an area of 8cm×9cm.
[0017] Compared with the existing technology, the present invention has the following specific advantages:
[0018] (1) Electrolyte additives are the most promising modification method to improve the performance of zinc-ion batteries. They are simple to operate and have obvious effects.
[0019] (2) Alum as an additive is low-cost, highly safe, non-toxic and harmless, and environmentally friendly.
[0020] (3) The present invention introduces alum into the electrolyte, which plays an important role in the modification of the anode of zinc ion batteries. On the zinc anode side, the zinc-aluminum alloy protective layer formed in situ has a uniform electric field to reduce the generation of dendrites and isolate water from the electrode surface to reduce water-induced side reactions. At the same time, high-valent aluminum ions compete with zinc ions for solvation in the aqueous electrolyte and play a positive role, effectively reducing the side reactions caused by solvated water molecules. The cycle life and reversibility of zinc ion batteries are improved.
[0021] (4) Alum additives can also stabilize vanadium-based compound cathodes. Aluminum-containing CEI can inhibit the accumulation of inert byproducts (Zn4SO4(OH)6nH2O) and the dissolution of vanadium-based compound cathodes. The cycle reversibility and rate performance of zinc-vanadium full batteries assembled using alum-additive electrolytes and different vanadium-based compound cathodes (vanadium dioxide, vanadium pentoxide, and ammonium vanadate) were significantly improved. Specifically, the Zn||VO2 full battery at 5Ag -1 After 3000 cycles at a current density of -1 The capacity retention rate exceeds 80%. Zn||V2O5 and Zn||NVO full batteries also show good cycling stability at 5A g -1After 1000 cycles under the conditions of -1 and 210mAh g -1 , the capacity retention rates are 80% and 94% respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a calculation diagram of the binding energy between ions and water in the electrolyte obtained in Example 1.
[0023] Figure 2 This is the XRD diagram of the zinc anode after the electrolyte obtained in Example 1 is assembled into a battery and cycled.
[0024] Figure 3 This is a SEM image of the zinc anode after the electrolyte obtained in Example 1 is assembled into a battery and cycled.
[0025] Figure 4 This is an AFM image of the zinc anode after the electrolyte obtained in Example 1 was assembled into a battery and cycled.
[0026] Figure 5 The electrolyte obtained in Example 1 was assembled into a symmetrical battery at 4 mA cm -2 @1mAh cm -2 Cycling performance diagram at current density of .
[0027] Figure 6 The Zn||VO2 full battery assembled from the electrolyte obtained in Example 1 is 5Ag -1 Cycling performance diagram at different current densities.
[0028] Figure 7 The Zn||V2O5 and Zn||NVO full battery assembled from the electrolyte obtained in Example 1 was used in 5Ag -1 Constant current cycling performance diagram under different current densities. DETAILED DESCRIPTION
[0029] Example 1
[0030] A certain amount of zinc sulfate solid (2.904 g) was weighed and dissolved in 5 mL of deionized water by ultrasonication to prepare a zinc sulfate solution with a concentration of 2 mol L -1 ; Take an appropriate amount of alum additive (190.71 mg) and add it to the above zinc sulfate solution, and ultrasonicate until the solution is clear and transparent to prepare an aqueous composite electrolyte containing alum;
[0031] Attached Figure 1The relative binding energy calculation diagram of different metal ions and water. It can be seen from the figure that aluminum ions and water (-6.48eV) have stronger binding energy than zinc ions and water (-0.64eV) and potassium ions and water (-0.40eV). The more highly coordinated high-valent aluminum ions tend to compete with zinc ions for dissolved water, effectively reducing the side reactions caused by solvated water molecules. Figure 2 The XRD diagram of the zinc anode after the electrolyte obtained in Example 1 and the zinc sulfate electrolyte were assembled into a symmetric battery and cycled. It can be seen from the figure that in the zinc sulfate electrolyte, the peak of the byproduct (Zn4(OH)6SO4-5H2O) appears on the surface of the zinc anode, and Zn4(OH)6SO4-5H2O is the main byproduct of zinc corrosion in weakly acidic electrolytes. However, when circulating in the zinc sulfate-alum electrolyte, there is no obvious diffraction peak related to Zn4(OH)6SO4-5H2O on the surface of the zinc anode. Figure 3 This is a SEM image of the zinc anode after cycling in a symmetric battery assembled using a modified electrolyte. It can be seen from the image that the zinc foil surface after cycling has a uniform metal nanosheet coating, without the formation of byproducts and dendrites. Figure 4 The AFM images show that the surface of the zinc anode in the zinc sulfate-alum electrolyte is relatively uniform and compact, without large protrusions corresponding to zinc dendrites. Therefore, the Zn||Zn symmetric battery assembled using the aqueous composite electrolyte containing alum has a good performance at 4 mA cm -2 @1mAh cm -2 The cycle life is up to 3000 hours under the condition Figure 5 )
[0032] The above-mentioned aqueous composite electrolyte containing alum was introduced, zinc metal sheet was used as anode, VO2 was used as cathode material, and Whatman GF / A was used as separator to assemble a CR2032 type Zn||VO2 full battery. The Zn||VO2 full battery was tested under different conditions and found to exhibit excellent electrochemical performance. When the current density was 5Ag -1 When using zinc sulfate-alum electrolyte, the Zn||VO2 full battery still has a specific capacity of 210 mAh g after 3000 cycles. -1 , its capacity retention rate exceeds 80% ( Figure 6 ). The stability of other vanadium-based cathode materials in zinc sulfate-alum electrolyte was also tested. Zn||V2O5 full cell and Zn||NVO full cell in 5Ag -1 After 1000 cycles under the conditions of -1 and 210mAh g -1 , the capacity retention rates are 80% and 94% respectively ( Figure 7 ), these results demonstrate the general applicability of using alum to inhibit the dissolution of vanadium-based cathodes.
[0033] Example 2
[0034] A certain amount of zinc sulfate solid (4.356 g) was weighed and dissolved in 5 mL of deionized water by ultrasonication to prepare a zinc sulfate solution with a concentration of 3 mol L -1 ; Take an appropriate amount of alum additive (47.68 mg) and add it to the above sulfuric acid solution, and ultrasonicate until the solution is clear and transparent to prepare an aqueous composite electrolyte containing alum;
[0035] The above zinc sulfate-alum mixed electrolyte was introduced, zinc sheets were used as electrodes, Whatman GF / A was used as a separator, and a zinc||zinc symmetric battery was assembled.
[0036] The above-mentioned zinc sulfate-alum mixed electrolyte was introduced, and the battery outer packaging body was made of aluminum-plastic film. A single zinc sheet with an area of 6cm×6cm was used as the anode, and a total of 6 sheets were made. A single vanadium-based compound with an area of 5cm×5cm was used as the cathode, and a total of 5 sheets were made. The single glass fiber separator had an area of 7cm×7cm, and a total of 10 sheets were made. The cathode, separator, and anode were stacked in sequence to assemble into a zinc-vanadium soft-pack battery with an area of 8cm×9cm.
[0037] Example 3
[0038] Weigh a certain amount of zinc chloride solid (2.04 g) and dissolve it in 5 mL of deionized water by ultrasonication to prepare a zinc chloride solution with a concentration of 3 mol L -1 ; Take an appropriate amount of alum additive (95.36 mg) and add it to the above zinc chloride solution, and ultrasonicate until the solution becomes clear and transparent to prepare an aqueous composite electrolyte containing alum;
[0039] The above zinc chloride-alum mixed electrolyte was introduced, zinc foil was used as electrode, Whatman GF / A was used as separator, and a zinc||zinc symmetric battery was assembled.
[0040] The above-mentioned zinc chloride-alum mixed electrolyte was introduced, and zinc foil was used as the anode, ammonium vanadate was used as the cathode material, and Whatman GF / A was used as the separator to assemble a zinc||ammonium vanadate full battery (CR2032 type).
[0041] The above-mentioned zinc chloride-alum mixed electrolyte was introduced, and the battery outer packaging body was made of aluminum-plastic film. A single piece of zinc foil with an area of 6 cm×6 cm was used as the anode, and a total of 6 pieces were made. A single piece of ammonium vanadate with an area of 5 cm×5 cm was used as the cathode, and a total of 5 pieces were made. The single piece of glass fiber separator had an area of 7 cm×7 cm, and a total of 10 pieces were made. The cathode, separator, and anode were stacked in sequence to assemble into a zinc||ammonium vanadate soft-pack battery with an area of 8 cm×9 cm.
[0042] Example 4
[0043] A certain amount of zinc trifluoromethanesulfonate solid (2.25 g) was weighed and dissolved in 5 mL of deionized water by ultrasonication to prepare a zinc trifluoromethanesulfonate solution with a concentration of 3 mol L -1 ; Take an appropriate amount of alum additive (143.03 mg) and add it to the above zinc trifluoromethanesulfonate solution, and ultrasonicate until the solution is clear and transparent to prepare an aqueous composite electrolyte containing alum;
[0044] The above zinc trifluoromethanesulfonate-alum mixed electrolyte was introduced, zinc powder was used as an electrode, Whatman GF / A was used as a separator, and a zinc||zinc symmetric battery was assembled.
[0045] The above-mentioned zinc trifluoromethanesulfonate-alum mixed electrolyte was introduced, zinc powder was used as the anode, V2O5 was used as the cathode material, and Whatman GF / A was used as the separator to assemble a zinc||V2O5 full battery (CR2032 type).
[0046] The above-mentioned zinc trifluoromethanesulfonate-alum mixed electrolyte was introduced, the single-piece area of the zinc powder electrode was 6cm×6cm, and a total of 6 pieces were made. The single-piece area of the vanadium pentoxide cathode sheet was 5cm×5cm, and a total of 5 pieces were made. The single-piece area of the glass fiber separator was 7cm×7cm, and a total of 10 pieces were made. The cathode, separator, and anode were stacked in sequence to assemble into an aqueous zinc||V2O5 soft-pack battery with an area of 8cm×9cm.
[0047] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing an electrolyte capable of synergistically regulating the cathode and anode interfaces of an aqueous zinc-vanadium battery, the preparation steps of which are as follows: (1) Under the assistance of ultrasound, the water-soluble zinc salt solid is completely dissolved in deionized water and cooled to room temperature to obtain a zinc salt solution with a concentration of 0.3-3.0 mol L -1 ; (2) adding an appropriate amount of alum potassium aluminum sulfate additive to the zinc salt solution of step (1), stirring until clear and transparent, to prepare an aqueous electrolyte; (3) Preparation of aqueous reversible zinc-vanadium full battery: zinc metal is used as the anode, vanadium-based compound is used as the cathode material, glass fiber is used as the separator, and the aqueous electrolyte prepared in step (2) is introduced to assemble into a button battery or a soft-pack battery.
2. The method for preparing an electrolyte capable of synergistically regulating the cathode and anode interfaces of an aqueous zinc-vanadium battery according to claim 1, characterized in that: Water-soluble zinc salts include zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride or zinc perchlorate.
3. The method for preparing an electrolyte capable of synergistically regulating the cathode and anode interfaces of an aqueous zinc-vanadium battery according to claim 1, characterized in that: The concentration of water-soluble zinc salt in the electrolyte is 1.5-2.5 mol L -1 The concentration of potassium aluminum sulfate additive is 5-100mmol L -1 .
4. The method for preparing an electrolyte capable of synergistically regulating the cathode and anode interfaces of an aqueous zinc-vanadium battery according to claim 1, characterized in that: Zinc metal includes zinc foil, zinc flakes or zinc powder.
5. The method for preparing an electrolyte capable of synergistically regulating the cathode and anode interfaces of an aqueous zinc-vanadium battery according to claim 1, characterized in that: The vanadium-based compound cathode includes vanadium dioxide, ammonium vanadate or vanadium pentoxide; wherein the vanadium dioxide cathode material is prepared by the following method: 0.1-30g of acetylacetonato vanadyl is dispersed in a certain amount of deionized water, 0.01-10g of sodium dodecyl sulfate is added after stirring, and then a certain amount of graphene oxide solution is dripped into the above solution, wherein the mass of graphene oxide in the graphene oxide solution is 0.005-3g, and after stirring for 0.5h, the solution is transferred to a 0.1-5L polytetrafluoroethylene liner, and a high-temperature reactor is assembled and heated at 160-21 The method comprises the following steps: heating the mixture at a constant temperature of 0°C for 6-48 hours, and then centrifuging, washing, and drying the precipitate to obtain a vanadium dioxide cathode material; and the ammonium vanadate cathode material is prepared by the following method: dispersing 0.2-10 mol of ammonium metavanadate in a certain amount of deionized water, stirring, adding 0.3-10 mol of oxalic acid dihydrate, stirring for 0.5 h, transferring the solution to a 0.1-1 L polytetrafluoroethylene liner, assembling a high-temperature reactor, and heating the mixture at a constant temperature of 160-210°C for 1-24 hours, and then centrifuging, washing, and drying the precipitate to obtain an ammonium vanadate cathode material.
6. The method for preparing an electrolyte capable of synergistically regulating the cathode and anode interfaces of an aqueous zinc-vanadium battery according to claim 1, characterized in that: The vanadium-based compound cathode electrode sheet described is prepared by the following method: 70wt% of the vanadium-based compound, 20wt% of acetylene black and 10wt% of polyvinylidene fluoride are mixed in N-methylpyrrolidone solvent, and a cathode slurry is obtained after ball milling for 1 hour. The cathode slurry is coated on a titanium foil current collector and vacuum dried at 80°C for 10 hours to prepare a cathode electrode sheet, wherein the mass loading of the active material vanadium oxide is 1 to 30.0 mg cm -2 .
7. Application of the electrolyte capable of synergistically regulating the cathode and anode interfaces of aqueous zinc-vanadium batteries prepared by the preparation method according to any one of claims 1 to 6, characterized in that: A button cell for assembling an aqueous zinc-vanadium battery, the assembly method is as follows: zinc metal is used as an anode, the vanadium-based compound electrode sheet prepared in claim 6 is used as a cathode, glass fiber is used as a diaphragm, and an aqueous electrolyte prepared by the preparation method described in any one of claims 1 to 3 is introduced to assemble into a CR2032 type button cell.
8. Application of the electrolyte capable of synergistically regulating the cathode and anode interfaces of aqueous zinc-vanadium batteries prepared by the preparation method according to any one of claims 1 to 6, characterized in that: A soft-pack battery for assembling an aqueous zinc-vanadium battery, the assembly method is as follows: an aluminum-plastic film is used to make a battery outer packaging body, the single-piece area of the zinc metal anode is 6cm×6cm, and a total of 6 pieces are made, a single-piece area of a vanadium-based compound cathode sheet is 5cm×5cm, and a total of 5 pieces are made, a single-piece area of a glass fiber separator is 7cm×7cm, and a total of 10 pieces are made, and the cathode, separator, and anode are stacked in sequence, and an aqueous electrolyte prepared by the preparation method according to any one of claims 1 to 3 is introduced to assemble to obtain an aqueous zinc-vanadium soft-pack battery with an area of 8cm×9cm.
Citation Information
Patent Citations
Acidic lead-zinc storage battery
CN105390754A
Method for increasing voltage of zinc-ion battery
CN110655114A
Aqueous zinc ion battery and method for protecting zinc negative electrode thereof
CN116454420A
Aqueous zinc ion battery electrolyte and aqueous zinc ion battery
CN118017034A
